Timmy Failure. Mistakes were made - Pastis, Stephan (Somerville, Mass : Candlewick Press, 2013)
Meet Timmy Failure, the founder, president, and CEO of the best detective agency in town, probably the nation. And his lazy sidekick, Total, a 1,500-pound polar bear.
Keywords: Private investigators -- Juvenile fiction; Polar bear -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous stories; Detective and mystery stories